Accelerated clinical response achieved by combining short-term tumor-directed photodynamic therapy with immunotherapy-based systemic therapies in synchronous colorectal cancer with MSI-H and POLE mutation: a case report - Wang, Yuhan; Gao, Lei; Ma, Bin; Shi, Jianming; Yin, Zhenyu; Zhu, Weidong; Chen, Hao (Frontiers in Immunology, 2024)
Genetic sequencing has revolutionized immunotherapy in colorectal cancer (CRC). Recent clinical trials have revealed a positive response to immunotherapy-based systemic therapies in CRC patient subgroups with microsatellite instability (MSI)-High or DNA polymerase epsilon (POLE) mutation. However, the unsatisfactory response rates was the major limitation in real-world practice of the precision immunotherapy in CRC. Adding photodynamic therapy (PDT) to systemic immunotherapy has showed synergetic anti-tumor effect by modulating tumor microenvironment, while the eligible patient's subgroups which would benefit from this combination remained equivocal. Here we reported a synchronous colorectal cancer patient with MSI-High and POLE mutation who had accelerated response in less than 2 cycles (42 days) of immunotherapy-based systemic therapies after tumor-directed PDT and has remained progression-free by far. This case enlightened the synergetic effect of PDT in immunotherapy-treated CRC patients, with the MSI and POLE-mutation status as predictors of survival benefits.